Análisis del desarrollo de competencias científicas para la enseñanza - aprendizaje de Química Inorgánica en los estudiantes del tercer semestre de la Carrera de Biología, Química y Laboratorio, Universidad Nacional de Chimborazo, periodo Abril – Agosto 2016. - Buñay Dumancela, Segundo Feliciano (2017)
The objective of this research was to analyze the development of scientific competences for the teaching and learning of Inorganic Chemistry in the Third Semester of the Biology, Chemistry and Laboratory at the Universidad Nacional de Chimborazo, from April - August 2016. The study is important because current education demands changes to train "competent" people with the capacity to learn to learn, to learn to relate to others, to learn to solve problems of daily life and to learn to live with oneself, through the updating of Knowledge that renews itself permanent way. The problem of scientific competence refers to the capacity to acquire and generate knowledge; but how that capacity contributes, beyond the specific practices of the sciences, to enrich and train the formation of the individual. The study aims to overcome the fragmentation of learning, applied non- experimental, diagnostic, exploratory and explanatory design focused on the analysis and interpretation of the variables. It is a descriptive study because it describes the existing knowledge on the subject. In the survey carried out on students of the third semester of the Biology, Chemistry and Laboratory at the Universidad Nacional de Chimborazo state that 68% do not know about the scientific competences, therefore it is recommended to the teachers to promote the importance of the application of the scientific competences in the students during the course of the race.